Philanthropic Practices of Rural Banks: A Case Study - Roslinda, Jay Alvarico (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study investigates the philanthropic corporate social responsibility (CSR) practices of rural banks and their effects on societal development, employee welfare, and institutional sustainability. Using qualitative data collected from respondents across three rural banks, the study identified 24 open codes, 8 categories, and 3 major themes. Findings reveal that rural banks strategically implement CSR programs—such as livelihood training, educational initiatives, community outreach, and environmental activities—to promote community empowerment and socio-economic development. These initiatives enhance clients’ financial literacy, income-generating capacities, and overall well-being, positioning rural banks as vital agents of local development. Internally, CSR engagement fosters employee morale, satisfaction, and organizational loyalty by strengthening alignment between personal values and institutional missions. The consistent support of bank leadership ensures the long-term sustainability and institutionalization of CSR initiatives. Two central outcomes of CSR emerged: growth, reflected in increased product awareness, financial performance, and customer retention; and relationships, manifested through stronger employee engagement and stakeholder trust. Despite logistical constraints, CSR efforts remained effective and impactful across participating institutions. The study concludes that philanthropic CSR in rural banking transcends mere compliance or goodwill—it serves as a strategic lever for organizational resilience and community advancement. The research contributes to the growing discourse on CSR in developing economies by providing empirical insights into how socially responsible practices can simultaneously drive sustainable development and institutional competitiveness within the rural banking sector.